2019
DOI: 10.1002/chem.201900383
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic, Aggregation, and Redox Properties of Double‐Rotor Boron Difluoride Hydrazone Dyes

Abstract: We develop the chemistry of boron difluoride hydrazone dyes (BODIHYs) bearing two aryl substituents and explore their properties. The low‐energy absorption bands (λmax=427–464 nm) of these dyes depend on the nature of the N‐aryl groups appended to the BODIHY framework. Electron‐donating and extended π‐conjugated groups cause a redshift, whereas electron‐withdrawing groups result in a blueshift. The title compounds were weakly photoluminescent in solution and strongly photoluminescent as thin films (λPL=525–578… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 69 publications
4
49
0
Order By: Relevance
“…None of the complexes 11 a – d described exhibited significant solvatochromism that would be expected for transitions with significant charge‐transfer character. The low Φ em values estimated for 11 a – 11 d are likely due to the free rotation of their N ‐aryl substituents in solution, which was observed previously for structurally related BODIHY monomers …”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…None of the complexes 11 a – d described exhibited significant solvatochromism that would be expected for transitions with significant charge‐transfer character. The low Φ em values estimated for 11 a – 11 d are likely due to the free rotation of their N ‐aryl substituents in solution, which was observed previously for structurally related BODIHY monomers …”
Section: Resultssupporting
confidence: 57%
“…The incorporation of electron‐donating substituents in 11 b (R 1 , R 2 =OMe) led to a red shift (Δ λ max =+20 nm) in the low‐energy absorption band, while the introduction of electron‐withdrawing substituents in 11 c (R 1 , R 2 =CF 3 ) resulted in a blue shift (Δ λ max =−10 nm). The molar extinction coefficients ( ϵ ) of 11 a – d in THF range between 20 500 and 33 800 m −1 cm −1 and are larger than those obtained for structurally related BODIHY monomers . Dimer 11 a had a low‐energy emission maximum ( λ em ) at 557 nm and Φ em =1 %, while 11 b (Δ λ em =+29 nm, Φ em <1 %) and 11 c (Δ λ em =−24 nm, Φ em =2 %) exhibited similar characteristics that followed the trends in absorption properties discussed above.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…[ 12 ] We have recently found that dual‐rotor BODIHYs 8b and BODIHY dimers 9 exhibit tunable redox properties dependent on the electronic nature of the N ‐aryl substituents and exhibit AIE (Figure 1). [ 13 ] Motivated by these findings, we have developed the first polymer containing BODIHY units in an effort to expand the functionality of these unique molecular, and now macromolecular, materials. It is envisioned that the incorporation of BODIHYs into polymers will alter their film‐forming properties and solution characteristics, thus providing an outlet for their potential use in organic electronics and biological applications.…”
Section: Figurementioning
confidence: 99%